New Executive Vice President of the DLSU Professional Schools, Inc. - De La Salle University, Manila (Animo Repository, 2002)
For school year 2002-2003, Francisco del Rosario, Jr., former Development Bank of the Philippines chairperson, is new Executive Vice President of the DLSU Professional Schools, Inc. He also assumes the position of Senior Financial Adviser of the DLSU System. Francisco replaces Federico Gonzalez.